Thrombotic Risk in the Antiphospholipid Syndrome - Lim, Wendy (Seminars in Thrombosis and Hemostasis, 2014)
The antiphospholipid syndrome (APS) is characterized by venous or arterial thrombosis and/or pregnancy morbidity in patients with persistent presence of antiphospholipid antibodies (aPL). Patients who are diagnosed with APS are identified to have a high risk of recurrent thrombosis, which can occur despite anticoagulant therapy. The optimal type, intensity, and duration of anticoagulant therapy for the treatment of APS remain controversial issues, particularly for arterial thrombosis and recurrent thrombosis. Patients with persistently positive testing for lupus anticoagulant and elevated levels of anticardiolipin antibodies and anti-β2 glycoprotein I antibodies—known as triple positivity—appear to be at increased risk for thrombosis compared with patients who test positive for a single aPL. Recognizing that patients with APS may potentially have different thrombotic risk profiles may assist clinicians in assessing the risks, benefits, and optimal duration of anticoagulation. Future studies that delineate thrombotic risk in APS and evaluate current and novel anticoagulants as well as nonanticoagulant therapies are required.
Keywords: antiphospholipid antibodies; lupus anticoagulant; anticardiolipin antibodies; anti-β2-glycoprotein I antibodies; antiphospholipid syndrome